2022
DOI: 10.1093/molbev/msac205
|View full text |Cite
|
Sign up to set email alerts
|

Coemergence of the Amphipathic Helix on Ameloblastin With Mammalian Prismatic Enamel

Abstract: To investigate correlation between the ameloblastin (Ambn) amino acid sequence and the emergence of prismatic enamel, a notable event in the evolution of ectodermal hard tissues, we analyzed Ambn sequences of 53 species for which enamel microstructures have been previously reported. We found that a potential amphipathic helix (AH) within the sequence encoded by exon 5 of Ambn appeared in species with prismatic enamel, with a few exceptions. We studied this correlation by investigating synthetic peptides from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…Remarkably, the N-terminal region of Ambn exon 5 also includes an evolutionarily conserved Y/F-x-x-Y/L/F-x-Y/F motif that mediates self-assembly in Amel, Ambn, and other intrinsically disordered proteins [ 27 ] and could conceivably drive Amel–Ambn co-assembly. Collectively, studies uncovering Ambn–membrane [ 7 , 25 , 26 ] and Amel–Ambn [ 28 , 29 , 30 ] interactions support the notion that the N-terminal region of Ambn exon 5 associates both with membranes and with Amel in addition to being involved in Ambn self-assembly.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Remarkably, the N-terminal region of Ambn exon 5 also includes an evolutionarily conserved Y/F-x-x-Y/L/F-x-Y/F motif that mediates self-assembly in Amel, Ambn, and other intrinsically disordered proteins [ 27 ] and could conceivably drive Amel–Ambn co-assembly. Collectively, studies uncovering Ambn–membrane [ 7 , 25 , 26 ] and Amel–Ambn [ 28 , 29 , 30 ] interactions support the notion that the N-terminal region of Ambn exon 5 associates both with membranes and with Amel in addition to being involved in Ambn self-assembly.…”
Section: Introductionmentioning
confidence: 68%
“…This sequence forms an amphipathic helix (AH) in the presence of phospholipid bilayer membrane vesicles in vitro [ 25 ] and binds to ameloblast-like cell plasma membranes [ 7 ]. A comprehensive study of Ambn’s secondary structure across animal species each carrying prismatic, nonprismatic, or no enamel showed that prismatic enamel formation strongly correlates to this AH-forming sequence and its ability to interact with membranes [ 26 ]. Remarkably, the N-terminal region of Ambn exon 5 also includes an evolutionarily conserved Y/F-x-x-Y/L/F-x-Y/F motif that mediates self-assembly in Amel, Ambn, and other intrinsically disordered proteins [ 27 ] and could conceivably drive Amel–Ambn co-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…This observation can be the result of loss of AMBN -cell binding, ( Su et al, 2020 ), or AMBN self-assembly ( Wald., et al, 2017 ). AMBN exon 5 encoded region contains the amphipathic helix (AH) cell binding domain that recently was found to be highly conserved among mammals and had a strong evolutionary relationship with enamel prismatic structure ( Su et al, 2022 ). The same region contains the Y/F-x-x-Y/L/F-x-Y/F self-assembly motif, and the disruption of this motif resulted in a perturbed enamel prismatic architecture ( Wald et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy could be due to the differences in the height of the secretory stage ameloblasts in fully developed enamel organs compared to the individual cells in 3D culture. We have recently reported that the addition of functional AMBN to LS-8 cells in culture resulted in an upregulation of planar cell polarity protein Vangl2 (2.8 times) and cell polarity protein Par-3 (3.8 times) when compared to controls (heat denatured AMBN and AMBN Δ5) ( Su et al, 2022 ). Vangl2 planar cell polarity protein is highly expressed particularly in the Tomes’ processes of secretory stage ameloblasts ( Nishikawa and Kawamoto, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation